Moderasi Oikumenis Melalui Khotbah Dukacita Dengan Konten Eskatologis Yang Universal - Twin Yoshua R. Destyanto; Rikardo P. Sianipar (Sekolah Tinggi Teologi Internasional Harvest Tangerang, 2022)
The ecumenical movement is workded to create harmony within the Christians. Effort that can be done is to moderate through funeral sermons, because there are potential differences on the eschatology views, which is often used as funeral sermons content. This raises the urgency to formulate the ecumenical funeral sermons. Therefore, this research aimed to explore the experiences of preachers from various denominations, who have delivered funeral sermons, then look for common ground for funeral sermons content, where all Christian denominations can accept the content. This study uses qualitative method with structured literature study and phenomenology approaches by interviewing three servants of God who had preached in funeral ceremony, from Protestant/Lutheran, Evangelical, and Pentecostal denominations. The results in this study indicate that funeral sermons, as part of pastoral care, need to be prepared and thought out so that they contain messages of comforts and at the same time bring unity to all listeners. Funeral sermons that bring hope to listeners should be filled with biblical verses that inspire faith and keep them walking in the truth. The possible eschatological message to preach is about the existence of hell and heaven, which all Christians, and most of the world's religions, believe in.